Sulla (Hedysarum coronarium L.) seed production at different sowing rates - Sulas L.; Ledda M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Sulla is a short-lived perennial legume native to the Mediterranean basin and grown as a rainfed forage crop in many countries on clay and calcareous soils. This legume has a remarkable N-fixation ability and can play an important role for forage production, due to its moderate condensed tannin content, and/or multifunctional agriculture (organic agriculture, environment protection, honey production, landscape embellishment, etc.). The objective of this research was to study, during a biennial cycle, the effect of different sowing rates (10, 20 and 30 kg/ha of seed) on sulla seed production and components in order to identify optimal plant density. The different seed rates showed a temporary effect in plant density and no significant effects on seed production compared to the age of the sulla stand.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)